Exploratory analysis of nutrient composition of adult and senior dog diets - German, Kyle; Melgoza, Cynthia; Torres-Henderson, Camille (Frontiers in Veterinary Science, 2025)
IntroductionSenior dog foods are often marketed as distinct from adult formulations, yet no specific nutrient profiles exist for this life stage. This study evaluated nutrient composition of over-the-counter adult and senior canine diets in relation to Association of American Feed Control Officials (AAFCO) adult maintenance requirements.MethodsSixty-one dry and canned diets were purchased from retail stores and complete proximate analysis with minerals was performed. The diets selected consisted of 25 brands (companies), including 30 diets marketed for adults (21 dry, 8 canned, and 1 freeze-dried) and 31 diets marketed for seniors (25 dry, 6 canned). Diets were randomly selected using a random number generator from the complete inventory of dog foods available at two pet food stores in Fort Collins, Colorado (one national retailer and one locally owned store). Nutrients were expressed per 1,000 kcal metabolizable energy, and descriptive statistics were generated. Adult vs. senior, dry vs. canned, and combined categories were compared using parametric or non-parametric tests depending on distribution. Within each company, paired adult and senior products were also evaluated for percent change in nutrient content.ResultsEighteen percent (18%; 11/61) of products did not meet at least one requirement for AAFCO adult maintenance, and differences between adult and senior diets were inconsistent. Fiber, fat, and energy density showed the greatest variability, especially among canned diets.DiscussionAs a descriptive exploratory analysis, no power calculation or adjustment for multiple comparisons was performed, and results should be interpreted as hypothesis generating. Overall, senior dog diets demonstrated wide variability and did not consistently differ from adult products, underscoring the challenge with not having defined nutrient profiles for this life stage, and the need for further research linking diet composition to clinical outcomes in aging dogs.